Literatura e cinema: uma leitura e interpretação das personagens de Dom Quixote de la Mancha e Sancho Pança como imagens - Italo Oscar Riccardi Leon (2015)
Within the intertextual comparative dialogic relations that permeate the correlations between literature and cinema, emerged the interest in studying figures/ characters of 'Don Quixote' and 'Sancho Panza' as emblematic images of classical Hispanic work, 'The ingenious nobleman Don Quixote de la Mancha', from Miguel de Cervantes, and also in the filmic version of 'Don Quixote', from the Russian filmmaker Gregory Kozintsev held in the fifties, with the primary purpose of questioning another possible look that can give new meaning to revisit them. Initially, the work talks about the approaches of literature and cinema as artistic language settings, and, soon after, examines the image as a visual representation and 'way of thinking', last idea that further aims to analyze and interpret some significant images of 'Don Quixote' and 'Sancho Panza'. Later, searching for a valid and unpublished theoretical and critical framework that enables to address 'Don Quixote' and 'Sancho Panza' images, from an intertextual comparative approach, were considered the theoretical contributions of Rancire and Didi-Huberman, whose analytical perspectives emphasize the need for another contemporary aesthetic regime in the interpretation and reading of images from artworks inserted in the compared literature propositions and other arts or other semiotic systems.